Novel Sinta Sasanti Karya Toti Tjitrawasita: Memahami Nilai-nilai Kehidupan Manusia - BM Sri Suwarni Rahayu (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
This article analyzes the novel Sinta Sasanti work by Toti Tjitrawasita in terms of structure and aspectsof the humanities. The method used approach is structural and pragmatic approach that focuses onaspects of the humanities. The results showed that the main character trying to achieve success. Basedon the study of human humanities should have a love for his parents, to others, to God and to theenvironment in order to create a harmonious life; humans should always realize the beauty in life inorder to be happy; human suffering must be steadfast in living and able to rise again; ideals futureneeds to be fought in order to achieve success.